2020
DOI: 10.1155/2020/9178973
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Anatomical Properties of Retromolar Canal in an Iranian Population: A Cone-Beam Computed Tomography Study

Abstract: Objectives. Retromolar canal (RC) is an anatomic structure, and due to increasing demand for surgical procedure in the retromolar area of the mandible, the identification of the retromolar canal has become an issue of clinical concern. It can innervate the third molar and some of the muscles around the posterior segment of the mandible, complicating surgical procedures in the retromolar area and root canal treatment of third molars. The aim of this study was to evaluate the incidence and anatomical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…(2013) ( 5 ). In our study, the observed prevalence was 23.1%, which coincides with other studies based on CBCT with similar sample sizes ( 8 , 19 ). There may be several causes for the different prevalence indicated by several studies, such as the applied anatomical definition of the RMC, different sample sizes in studies, samples’ distinct population origins, study designs, e.g.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…(2013) ( 5 ). In our study, the observed prevalence was 23.1%, which coincides with other studies based on CBCT with similar sample sizes ( 8 , 19 ). There may be several causes for the different prevalence indicated by several studies, such as the applied anatomical definition of the RMC, different sample sizes in studies, samples’ distinct population origins, study designs, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…According to the unilateral canals, we found that right canals were more frequent than left canals, just as Nikkerdar et al . reported, but with no significant differences ( 8 ). Nevertheless, higher prevalences have been described for left canals ( 5 , 21 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…They obtained different results: from the frequency of 1.7% (Ossenberg) to 75.4% (Patil et al). Such diverse results were obtained due to the use of dia gnostic techniques: CBCT, panoramic radiography and anatomical examinations on dry, macerated mandibles [5,10,[21][22][23][24][25][26][27]. As stated in the studies by Haas et al [6], the effectiveness of CBCT and CT in detecting the retromolar canal is almost four times higher than in the case of panoramic radiography.…”
Section: Discussionmentioning
confidence: 99%